Pengaruh Temperatur terhadap Kekuatan Impak Material Baja ST37 dengan Metode Charpy dan Izod - Jandri Fan; Sahat; Al Qadry; Eka Putra Dairi Boangmanalu; Angga Bahri Pratama (Jurnal INOVATOR, 2023)
Impact Test can be interpreted as a test that measures the ability of a material to accept impact loads which are measured by the amount of energy required to break the specimen with a swing. The aim of this test is to determine the effect of temperature on the value of energy absorbed by the material and the impact value. The method used in this research is the experimental method, namely the method used to find the effect of temperature on the impact strength of charpy and izod. The results of the charpy and izod impact tests on ST37 Steel specimens prove that there is an influence of temperature on the charpy and izod impact tests. Where the higher the temperature, the higher the energy absorbed and the impact price. Conversely, the lower the temperature, the energy absorbed and the impact price will be lower. In the test results, the lowest energy absorbed in the charpy impact test was 76 J and 22 J in the izod impact test, while the highest energy absorbed in the charpy impact test was 245 J and 114 J in the izod impact test. The lowest impact price in the test was 0.1727 J/mm2 for the charpy impact test and 0.037 J/mm2 for the izod impact test, while the highest impact price in the test was 0.5568 J/mm2 for the charpy impact test and 0.19 J/mm2 for izod impact testing.